Does Method of Placental Removal or Site of Uterine Incision Repair Alter Endometritis After Cesarean Delivery?. Issue 1 (1993) - Magann, Everett F.; Dodson, Mark K.; Harris, Robert L.; Floyd, Randall C.; Martin, James N.; Morrison, John C.
Abstract : Objective: his investigation was undertaken to evaluate the relationship between postcesarean endometritis and (1) method of placental removal and (2) site for uterine repair. Methods: This prospective, randomized study included 120 patients who underwent primary or repeat abdominal delivery for arrest of progress in labor, fetal distress, or breech presentation. Parturients were divided into four groups: I—spontaneous placental detachment, in situ uterine repair; II—spontaneous placental detachment, exteriorized uterine repair; III—manual placental removal, in situ uterine repair; and IV—manual placental removal, exteriorized uterine repair. Prophylactic antibiotics were not used. Results: Endometritis was significantly increased in the manual removal/exteriorized uterine repair group versus all the other groups including the spontaneous removal in situ (group I, P = 0.012), the spontaneous removal/exteriorized repair group (group II, P = 0.034), and the manual removal/in situ repair group (group III, P = 0.043). Comparison of group IV (manual removal/ exteriorized repair) with the combined groups I, II, and III (spontaneous removal/in situ repair, spontaneous removal/exteriorized repair, and manual removal/in situ repair) was significantly different ( P = 0.005). Prior to delivery, use of an internal monitoring system, skill of the operating surgeon, and type of anesthesia were similar among groups. Conclusions: The findings of this investigation suggest that; when other known causes of infectious morbidity are constant, manual placental remvol in association with exteriorization for uterine repair significantly increases postcesarean endometritis.